INTERACTION STUDY: THE EFFECT OF ORTHOSIPHON STAMINEUS EXTRACT ON HUMAN CYTOCHROME P450 - Purwantiningsih .; Abas Hj Hussin (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
Herbal remedies are often used concomitantly with prescribed medication, which leads to an increase in the potential of herb-drug interactions. Orthosiphon stamineus is one of the popular herbal preparations that is traditionally used, especially as a diuretic or for the elimination of kidney stones. The inhibitory effect of O. stamineus extract on human cytochrome P450 isoforms, namely CYP1A2, CYP3A4, CYP2C9 and CYP2D6, has been determined using luminescent methods. The final concentrations of O. stamineus extract tested were 0.01, 0.1, 1, 10, 100 and 1000µg/mL. IC50 value was used to assess the modulation potencies for each CYP isoform. The extract showed a moderate inhibition towards CYP2C9 with the IC50 of 20.12µg/mL and showed IC50 of 49.90, 89.24 and 97.82µg/mL for CYP1A2, CYP2D6 and CYP3A4, respectively. These data suggest that O. stamineus extract may potentiate the herb-drug interaction via CYP inhibition.